1998
DOI: 10.1037/0021-843x.107.3.375
|View full text |Cite
|
Sign up to set email alerts
|

Developmental antecedents of partner abuse: A prospective-longitudinal study.

Abstract: Prospective measures of risk factors for partner abuse were obtained from a large birth cohort in 4 domains: socioeconomic resources, family relations, educational achievements, and problem behaviors. Partner abuse outcomes were measured at age 21. Results showed that antecedents of abuse included risk factors from all 4 domains. Risk factors were similar for men and women. Some age 3 antecedents were significant, but the strongest correlations were from age 15. In multivariate analyses, the most consistent pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
358
7
8

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 320 publications
(409 citation statements)
references
References 61 publications
36
358
7
8
Order By: Relevance
“…A striking finding was the absence of sex differences in predictors of partner violence. These results are consistent with those observed elsewhere (e.g., Magdol et al, 1998a) and argue for the need to include both females and males in our partner violence prevention efforts. Studies with larger sample sizes will be needed to definitively establish whether sex differences exist in the population; at this time, however, the exclusive focus on males' risk factors is not supported.…”
Section: Prevention Implicationssupporting
confidence: 92%
“…A striking finding was the absence of sex differences in predictors of partner violence. These results are consistent with those observed elsewhere (e.g., Magdol et al, 1998a) and argue for the need to include both females and males in our partner violence prevention efforts. Studies with larger sample sizes will be needed to definitively establish whether sex differences exist in the population; at this time, however, the exclusive focus on males' risk factors is not supported.…”
Section: Prevention Implicationssupporting
confidence: 92%
“…The CTS yields violence prevalence and frequency scores for both perpetration and victimization . As in other community samples, we found that women reported as much or more violent perpetration compared with violent victimization (e.g., Magdol et al, 1998;Morse, 1995).…”
Section: Intimate Partner Violencesupporting
confidence: 53%
“…Generally, community surveys fi nd that about one in six couples experience IPV annually (Jouriles et al, 2001;Schafer et al, 1998;Straus and Gelles, 1990;Wolak and Finkelhor, 1998). Rates are higher among younger couples, cohabiting couples, and couples with children (Bardone et al, 1996;Magdol et al, 1998). McDonald et al (2006) estimated that "approximately 15.5 million American children live in dual-parent households in which partner-violence has occurred in the past year" (p. 139).…”
Section: Extent Of Intimate-partner-violence Exposure and Substance Usementioning
confidence: 99%
“…Longitudinal studies in high-income countries have established childhood experiences of violence as a causal factor for intimate partner violence (Capaldi and Clark 1998;Ehrensaft et al 2003;Magdol et al 1998;Swinford et al 2000). While no such studies have been completed in low-and middle-income countries, cross-sectional studies find a strong and consistent association between partner violence by men who experienced harsh physical punishment as a child and witnessed violence at home …”
Section: Restoring Paradise In the Caribbean: Combatting Violence Witmentioning
confidence: 98%
“…22 The connection is consistent with international literature that suggests that children who experience or witness violence are more likely than those who do not to perpetrate violence later in life (Capaldi and Clark 1998;Capaldi et al 2003;Fulu et al 2013;Kishor and Johnson 2004). Violent discipline has also been found to be more common in households affected by intimate partner violence than in households that are not (Bott et al 2012 Longitudinal studies in high-income countries have established childhood experiences of violence as a causal factor for intimate partner violence (Capaldi and Clark 1998;Ehrensaft et al 2003;Magdol et al 1998;Swinford et al 2000). While no such studies have been completed in low-and middle-income countries, cross-sectional studies find a strong and consistent association between partner violence by men who experienced harsh physical punishment as a child and witnessed violence at home (Heise 2011).…”
Section: Connecting Different Types Of Violencementioning
confidence: 99%